Patterns of disability benefit receipt and variations by psychiatric diagnosis: findings from a novel data linkage study - Ledden, Sarah; Hotopf, Matthew; Fear, Nicola; Stevelink, Sharon (International Journal of Population Data Science, 2025)
Aims Personal Independence Payment (PIP) was introduced as the new disability benefit in the UK among major benefit reforms in 2013. It is unknown how PIP has been allocated in populations with mental health conditions. We aim to explore how average duration and number of PIP spells differs by psychiatric diagnosis. Methods We used a linked dataset established by combining electronic secondary mental health records from South London and Department for Work and Pensions (DWP) administrative benefits data. Number of PIP spells, average number of days per PIP-benefit spell, and total number of days patients received PIP-benefit across all spells will be calculated for each individual. Multivariable linear and poisson regression models will be used to test associations between psychiatric diagnosis and PIP duration variables. Results 34,900 linked patients who accessed secondary mental healthcare services received PIP in the coverage window. 17,062 of these received PIP with no prior history of disability benefit receipt and were included in our analysis. 98% of patients received one continuous spell of PIP. Those with a diagnosis of intellectual disability and severe mood disorders received PIP for longer lengths of time. Patients with a diagnosis of drug or alcohol use disorders received PIP for a fewer number of days in the observation period. Conclusions PIP is awarded for a limited period of time, with most PIP awards granted for two years or less. Our findings could be used to inform frequency of reviews for disability benefit for certain psychiatric conditions to reduce individual burden and cost to the state.